Transcriptomic and metabolomic analysis reveals the molecular mechanism of exogenous melatonin improves salt tolerance in eggplants - Wang, Han; Zhang, Yu; Jiang, Haikun; Ding, Qiangqiang; Wang, Yan; Wang, Mingxia; Yan, Congsheng; Jia, Li (Frontiers in Plant Science, 2025)
IntroductionMelatonin significantly enhances the tolerance of plants to biotic and abiotic stress, and plays an important role in plant resistance to salt stress. However, its role and molecular mechanisms in eggplant salt stress resistance have been rarely reported. In previous studies, we experimentally demonstrated that melatonin can enhance the salt stress resistance of eggplants.MethodsIn this study, we treated salt-stressed eggplant plants with melatonin and a control treatment with water, then conducted physiological and biochemical tests, transcriptomic and metabolomic sequencing, and RT-qPCR validation at different stages after treatment.ResultsThe results showed that exogenous melatonin can alleviate the adverse effects of salt stress on plants by increasing the activity of antioxidant enzymes, reducing the content of reactive oxygen species in plants, and increasing the content of organic osmoprotectants. Transcriptomic and metabolomic data, as well as combined analysis, indicate that melatonin can activate the metabolic pathways of plant resistance to adverse stress. Compared to the control treatment with water, melatonin can activate the genes of the α-linolenic acid metabolism pathway and promote the accumulation of metabolites in this pathway, with significant effects observed 48 hours after treatment, and significantly activates the expression of genes such as SmePLA2, SmeLOXs and SmeOPR et al. and the accumulation of metabolites such as α-Linolenic acid, (9R,13R)-12-oxophytodienoic acid, 9(S)-HpOTrE and (+)-7-iso-Jasmonic acid. RT-qPCR validated the activating effect of melatonin on the candidate genes of the a-linolenic acid metabolism pathway.DiscussionThis study analyzed the molecular mechanism of melatonin in alleviating eggplant salt stress, providing a theoretical foundation for the application of melatonin in enhancing eggplant salt stress resistance in production.